2004
DOI: 10.1091/mbc.e04-04-0293
|View full text |Cite
|
Sign up to set email alerts
|

The Cochaperone HspBP1 Inhibits the CHIP Ubiquitin Ligase and Stimulates the Maturation of the Cystic Fibrosis Transmembrane Conductance Regulator

Abstract: The CHIP ubiquitin ligase turns molecular chaperones into protein degradation factors. CHIP associates with the chaperones Hsc70 and Hsp90 during the regulation of signaling pathways and during protein quality control, and directs chaperone-bound clients to the proteasome for degradation. Obviously, this destructive activity should be carefully controlled. Here, we identify the cochaperone HspBP1 as an inhibitor of CHIP. HspBP1 attenuates the ubiquitin ligase activity of CHIP when complexed with Hsc70. As a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
146
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 36 publications
6
146
0
Order By: Relevance
“…Based on previous studies showing that degradation of STUB1 substrates can be modulated by different HSPA8 co-chaperones [43][44][45] it is conceivable that STUB1-dependent degradation of HIF1A by CMA is regulated by HSPA8 co-chaperones. Moreover, it is also possible that STUB1 acts at the lysosome level, mediating the interaction between HIF1A and LAMP2A.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies showing that degradation of STUB1 substrates can be modulated by different HSPA8 co-chaperones [43][44][45] it is conceivable that STUB1-dependent degradation of HIF1A by CMA is regulated by HSPA8 co-chaperones. Moreover, it is also possible that STUB1 acts at the lysosome level, mediating the interaction between HIF1A and LAMP2A.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that HspBP1 is involved in the control of proteasomal activity by inhibition of CHIP ubiquitin ligase when it is complexed with Hsp70 (30). Recently it has been found that binding of HspBP1 to Hsp70 prevents inhibition of cathepsin-dependent death of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…HspBP1 is the least efficient as an NEF and is inhibitory of Hsc70 refolding function under all conditions tested. Biologically, HspBP1 promotes the degradation of proteins and blocks the anti-apoptotic function of stress-induced Hsp70 (44,45). These functions are consistent with HspBP1 acting as an inhibitor of Hsc70.…”
Section: Discussionmentioning
confidence: 99%